Hsp90 pan and Isoform-Selective Inhibitors as Sensitizers for Cancer Immunotherapy - Shiying Jia; Neeraj Maurya; Brian S. J. Blagg; Xin Lu (Pharmaceuticals)
The 90 kDa heat shock proteins (Hsp90) are molecular chaperones that regulate the stability and maturation of numerous client proteins implicated in the regulation of cancer hallmarks. Despite the potential of pan-Hsp90 inhibitors as anticancer therapeutics, their clinical development has been hindered by on-target toxicities, particularly ocular and cardiotoxic effects, as well as the induction of pro-survival, compensatory heat shock responses. Together, these and other complications have prompted the development of isoform-selective Hsp90 inhibitors. In this review, we discuss the molecular bases for Hsp90 function and inhibition and emphasize recent advances in isoform-selective targeting. Importantly, we highlight how Hsp90 inhibition can sensitize tumors to cancer immunotherapy by enhancing antigen presentation, reducing immune checkpoint expression, remodeling the tumor microenvironment, and promoting innate immune activation. Special focus is given to Hsp90β-selective inhibitors, which modulate immunoregulatory pathways without eliciting the deleterious effects observed with pan-inhibition. Preclinical and early clinical data support the integration of Hsp90 inhibitors with immune checkpoint blockade and other immunotherapeutic modalities to overcome resistance mechanisms in immunologically cold tumors. Therefore, the continued development of isoform-selective Hsp90 inhibitors offers a promising avenue to potentiate cancer immunotherapy with improved efficacy.